TIPOLOGI ISLAM DI INDONESIA: DIALEKTIKA AGAMA, BUDAYA DAN TRADISI LOKAL - Nanang Zamroji, Nanang; Nahdiyah , Umi; Nur Azizah, Munifa (Jurnal Pendidikan : Riset dan Konseptual, 2026)
Islam in Indonesia has evolved within a plural and dynamic socio-cultural context, producing distinctive patterns of religiosity that differ markedly from Islamic typologies found in other regions. The relatively peaceful process of Islamization, grounded in cultural approaches and sustained through engagement with local traditions and indigenous wisdom, has fostered a dialectical relationship between the normative teachings of Islam and existing cultural practices. This article aims to analyze the defining characteristics of Islamic typologies in Indonesia, identify the historical and social factors that shaped their formation, and explain the fundamental differences between Indonesian Islam and Islamic expressions elsewhere in the Muslim world. Using a qualitative library-based research design, the study applies historical-analytical and comparative strategies to examine relevant scholarly literature. The findings indicate that Indonesian Islam has developed as a moderate, inclusive, and contextual typology, reflected in cultural accommodation, interpretive flexibility, and a strong orientation toward social harmony. The dialectic between religion and culture emerges as a central mechanism shaping this distinctive Islamic character and differentiating it from more scripturalist and puritanical Islamic typologies in other regions. The article contributes to Islamic studies by affirming Indonesian Islam as a religious typology.